(untitled) (Inovasi: Jurnal Diklat Keagamaan, 2017)
Diversity (multicultural) is the reality of life. In Madrasah Aliyah, the mul ti cul tural phenomenon of students also occurs, due to ethnographic, demographi c and status variabl es. In Isl am, diversity is for li-taarofu, knowing and understanding and helping. Counseling assistance to students requires the competence of multicultural counseling (KKM). This study describes KKM Guru BK Madrasah Aliyah, including awareness, knowledge and skills of multicultural counseli ng and training program of teacher’s competence improvement BK. This research is a case study with qualitative descriptive. The subject of the research is the teacher of BK MA alumni of Counseling and Counseling Training at the Religious Training Center of Surabaya. Data collection using questionnaires and interviews. Data analysis was done descriptively qualitative. The results showed that, 14 % of teachers BK MA have low competence and 86% high. Mul ticultural counsel ing as a service to the multicultural client is also increasingly important, so that the training for the increased competence of the BK Teachers is required. Programs of training appropriate to the multicultural component of counseling and experimental learning model based on andragogy can be applied to BK Teachers. Increasing the competence of multicultural counseling needs to get the attention of Education Hall by designing curriculum and multicultural-oriented syllabus syllabus.